The impact of public policies on mental health in Latin America: a systematic review. - Nicolas Campodonico (Perspectivas Metodológicas​)
This work proposes to carry out a systematic review on the impact of public policies in the field of mental health in Latin America, to describe the theoretical and methodological approaches. The systematic review, according to the PRISMA Declaration, is carried out in August 2020 and twenty-five scientific articles are selected from 6 databases that refer to publications in Spanish between 2010-2020, where the importance of public policies is concluded in mental health on issues related to public health, disability, childhood and social inclusion, thus guaranteeing the essential human rights of each subject.